Klystron device - OKUBO YOSHIHISA; FUJII, YOSHIFUMI (2023)
Provided is a klystron device capable of improving output conversion efficiency. The klystron device comprises a klystron body and a focusing magnetic field device. The klystron body has an electron gun portion, a collector portion, a plurality of cavity resonators, and a plurality of drift tubes. The cavity resonator has end portions that face each other in the axial direction to form a gap portion that communicates with the drift tube. At least one of the cavity resonators has an electric field correction portion at a portion of the end portion, the electric field correction portion making the interval of the gap portion different from the interval at the end portion. 提供一种能够提高输出转换效率的速调管装置。速调管装置包括速调管主体和聚焦磁场装置。所述速调管主体具有电子枪部、集电极部、多个空腔谐振器以及多个漂移管。所述空腔谐振器具有端部，所述端部在轴向上彼此相对而形成与所述漂移管连通的间隙部。至少一个所述空腔谐振器在所述端部的一部分具有电场校正部，所述电场校正部使所述间隙部的间隔与端部处的间隔不同。